Determination of Biological Transmutation in Germination of Seeds - Kumar, Itagi Ravi (New Visions in Science and Technology Vol. 6, 2021)
The laws that govern biological reactions appear to be distinct from physical laws, and these laws do not apply to biological reactions. Nuclear reactions occur in the biological system at low temperatures equal to room temperature, withstanding by the biological system to create required elements from the available elements within the biological system. The objective of the study was to found out the biological transmutation in the germination of green gram and bengal gram in the form by increasing elements contents. Green gram and Bengal gram seeds were germinated at room temperature and in its natural environment. Optical emission spectrometry was used to analyse the elements in control and germinated seeds using the wet method. The results showed that Na increased by 417%, Al by 125%, Cr by 400%, Mn by 71.43%, Fe by 28.89% and Zn increased by 13% where was among decreased elements in germinated seeds with respect to control seeds Mg decreased by 14.60%, P by 4.57%, K by 10.16%, Ca by 24.59% and Cu decreased by 17.65% in green gram germinated seeds and while in bengal gram germinated seeds P increased by 8.48%, K by 22.40% and Zn increased by 10%. Among decreased elements in the germinated seeds with respect to control seeds Na decreased by 13.03%, Mg by 42.57%, Al by 36.35%, Ca by 6.13%, Mn by 40%, Fe by 22.22% and Cu by 12.5%. In green gram germinated seeds, the total of increasing and decreasing elements was 147 % increased and 10% decreased, while in Bengal gram germinated seeds, the total of increasing and decreasing elements was 20.48 % (1692 ppm) increased and 23.23 % (324 ppm) decreased.